Agitación al despertar y separación parental de pacientes pediátricos sometidos a cirugías programadas con anestesia general en Iquitos 2021 - Torres Marquina, Clara Solange (2022)
Agitation upon awakening is a frequent event that arises in pediatric patients after having undergone surgery under general anesthesia, which usually varies from 10% to 80%. Pre-surgical use of midazolam has been identified as anesthetic factors, this situation has a great impact and has been associated with various risk factors such as age, sex or preoperative anxiety, although its etiology is still unknown. It is important to highlight that recovery with agitation can lead to physical and psychological damage to the pediatric patient and prolong their hospital stay. We can note that the factors associated with agitation depend on the place of study. Our results will allow preventive interventions to be carried out in the preoperative period to reduce the negative effects in the pediatric patient. Currently, there are no protocols for the approach to agitation upon awakening from general anesthesia at the Regional Hospital of Loreto. The main objective of this work is to determine the risk factors associated with development in pediatric patients.